Styrene/Maleic Acid Copolymers Form SMALPs by Pulling Lipid Patches out of the Lipid Bilayer - Orekhov, Philipp S (Langmuir : the ACS journal of surfaces and colloids, 2019)
Amphiphilic copolymers composed of styrene and maleic acid (SMA) monomers caused a major methodical breakthrough in the study of membrane proteins. They were found to directly release phospholipids and membrane proteins both from artificial and natural lipid bilayers, yielding stable water-soluble discoidal SMA/lipid particles (SMALPs) of uniform size. Although many empirical studies indicate the great potency of SMALPs for membrane protein research, the mechanisms of their formation remain obscure. It is unknown which factors account for the very assembly of SMALPs and govern their uniform size. We have developed a coarse-grained (CG) molecular model of SMA copolymers based on the MARTINI CG force field and used it to probe the behavior of SMA copolymers with varying composition/charge/concentration in solution as well as their interaction with lipid membranes. First, we found that SMA copolymers tend to aggregate in solution into clusters, which could account for the uniform size of SMALPs. Next, molecular dynamics (MD) simulations showed that periodic SMA copolymers with styrene/maleic acid ratios of 2:1 ([SSM] n) and 3:1 ([SSSM] n) differently interacted with lipid bilayers. While clusters of 2:1 SMA copolymers induced membrane poration, the clusters of 3:1 SMA copolymers extracted lipid patches from the membrane yielding SMALP-like structures. Extraction of lipid patches was also observed when we simulated the behavior of 3:1 copolymers with varying lengths and statistical distribution of styrene and MA units. Analysis of MD simulation trajectories and comparison with experimental data indicate that the formation of SMALPs requires copolymer molecules with a sufficient number of units made of more than two sequential styrene monomers